Mixed Neuroendocrine Carcinoma and Hepatocellular Carcinoma: A Case Report and Literature Review - Lan, Jianwei; Guo, Deliang; Qin, Xian; Chen, Baiyang; Liu, Quanyan (Frontiers in Surgery, 2021)
ABSTRACT: Background: Neuroendocrine tumors are heterogeneous malignancies that originate from the neuroendocrine system. Previous studies show that this cancer type mainly localizes in the gastrointestinal tract and often metastasizes to the liver. Primary liver neuroendocrine tumors are very rare and primary hepatic neuroendocrine tumors (PHNET) with concurrent hepatocellular carcinoma (HCC) are extremely rare. To the best of our knowledge, only few PHNET cases have been identified, making their diagnosis difficult. Here, we report the biggest ever reported and “deceiving” lesion of a mixed neuroendocrine-non-neuroendocrine neoplasm in the liver, aiming to raise awareness and improve treatment of the disease. Case presention: Here, we report a preoperative misdiagnosed case that presented with hepatocellular carcinoma clinical features and no extrahepatic tumors. Postoperative pathology confirmed that it was a mixed neuroendocrine-non-neuroendocrine neoplasm. The patient was then referred for etoposide and cisplatin based chemotherapy. No disease recurrence was observed at the 6-month follow-up. Conclusion: We report a very rare and easily misdiagnosed case and we speculate that there were “undifferentiated cells” undergoing neuroendocrine and hepatocellular carcinoma differentiation, during which some hepatocellular carcinoma cells express neuroendocrine features. We recommend proper surgery and postoperative platinum-based chemotherapy in the management of this disease.